2015
DOI: 10.1038/ijo.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulation of hypothalamic and brown/beige adipose tissue activities in human obesity

Abstract: In humans, the increase in brown/beige adipose tissue activity related to body mass reduction occurs independently of changes in hypothalamic activity as determined by functional magnetic resonance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 46 publications
4
29
0
6
Order By: Relevance
“…Some individuals showed increases, whereas others showed no change or decreases in UCP1 and browning marker expression ( Figures 4A-4D, right, middle, and left, respectively). These inter-individual differences in WAT gene expression are coherent with the reported variability of response in BAT activity and WAT UCP1 mRNA expression during weight loss of a few individuals (Oliveira et al, 2016;Orava et al, 2013;Rachid et al, 2015;Vijgen et al, 2012;Nakhuda et al, 2016). Despite markedly different regulation of gene expression, the decrease in body fat (12%-13%) was similar in the three groups ( Figure 4E).…”
Section: Gene Expression Of Brown and Beige Markers In Subcutaneous Asupporting
confidence: 84%
See 1 more Smart Citation
“…Some individuals showed increases, whereas others showed no change or decreases in UCP1 and browning marker expression ( Figures 4A-4D, right, middle, and left, respectively). These inter-individual differences in WAT gene expression are coherent with the reported variability of response in BAT activity and WAT UCP1 mRNA expression during weight loss of a few individuals (Oliveira et al, 2016;Orava et al, 2013;Rachid et al, 2015;Vijgen et al, 2012;Nakhuda et al, 2016). Despite markedly different regulation of gene expression, the decrease in body fat (12%-13%) was similar in the three groups ( Figure 4E).…”
Section: Gene Expression Of Brown and Beige Markers In Subcutaneous Asupporting
confidence: 84%
“…As to whether the data reported on diet-induced weight loss can be extrapolated to bariatric surgery-induced weight loss is a more challenging question. Indeed, several studies recently reported bariatric surgery-induced BAT activation and WAT browning in the neck region (Neinast et al, 2015;Oliveira et al, 2016;Rachid et al, 2015;Vijgen et al, 2012). Beyond the aforementioned hypothetical opposite response to CR of distinct WAT depots, these apparently contradictory findings may be accounted for by the Data are mean ± SEM.…”
Section: Relevance and Limitations Of Studying Subcutaneous Abdominalmentioning
confidence: 99%
“…In addition, recent findings show that Roux-en-Y gastric bypass (RYGB) surgery leads to browning of gonadal WAT in female mice and this may be explained in part by the upregulation of ANP and BNP after RYGB (Neinast et al, 2015). Similar observations have been reported in humans undergoing RYGB surgery, although detailed mechanisms by which RYGB surgery promotes beige adipocyte biogenesis in supraclavicular adipose tissue are still unknown (Rachid et al, 2015). …”
Section: Heartsupporting
confidence: 75%
“…Similarly, body weight reduction by the Roux-en-Y gastric bypass (RYGB) was associated with an increase in BAT activity under cold. This increase in BAT activity levels appears to be independent of hypothalamic activity (Rachid et al, 2015). In mice, higher expression of UCP1 was observed in the gonadal WAT but not in the inguinal WAT after RYGB surgery.…”
Section: Human Batmentioning
confidence: 99%